Aerospace series. Nuts, hexagon, self-locking by plastic ring, normal height, normal across flats, in alloy steel, cadmium plated. Classification: 900 MPa (at ambient temperature) / 120 °C. (31st January 2017) - British Standards Institution,
No abstract available